Pathogenesis of spring viremia of carp virus in emerald shiner Notropis atherinoides Rafinesque, fathead minnow Pimephales promelas Rafinesque and white sucker Catostomus commersonii (Lacepede). Issue 6 (28th September 2015) - Misk, E; Garver, K; Nagy, E; Isaac, S; Tubbs, L; Huber, P; Al‐Hussinee, L; Lumsden, J S
Abstract: Spring viremia of carp (SVC) is a reportable disease to the World Organization of Animal Health (OIE) as it is known to cause significant international economic impact. In Canada, the first and only isolation of SVC virus (SVCV) was in 2006, from common carp Cyprinus carpio L., at Hamilton Harbour, Lake Ontario. The susceptibility of fathead minnow Pimephales promelas Rafinesque, emerald shiner Notropis atherinoides Rafinesque and white sucker Catostomus commersonii (Lacepede) to intraperitoneal injection of the Canadian isolate (HHOcarp06) was evaluated using experimental infection, virus isolation, quantitative reverse transcription polymerase chain reaction (qRT‐PCR), histopathology and immunohistochemistry (IHC). Emerald shiner and fathead minnow were most susceptible with 43 and 53% cumulative mortality, respectively, compared with koi at 33%. Quantitative RT‐PCR demonstrated that koi had high viral loads throughout the experiment. At 34 days post‐infection, SVCV was detected from sampled emerald shiner and white sucker in very low titre and was not detected from fathead minnow. Koi, fathead minnow and emerald shiner had gross lesions typical of SVC disease. The histopathological picture was mostly dominated by necrotic changes in kidney, spleen, liver, pancreas and intestine. IHC further confirmed SVCV infection, and staining was largely correlated with histological lesions.